EKSPRESI EMOSI MARAH PADA WAJAH MANUSIA DALAM SENI GRAFIS (RELIEF PRINT) - Mony Trimaharjo, Yofita Sandra, S.Pd., M.Pd., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2016)
Anger is a feeling of protest, shame insecurity or frustration toward someone or something, which is caused when the ego feels hurt or threatened. The intensity of anger, or lack thereof, is different between one human to another. Anger becomes the dominant flavors in behavioral, cognitive, and physiological when someone makes a conscious decision to take action to immediately stop the threatening behavior of another outside force. Anger can have physical and mental consequences.The purpose in making this thesis is to visualize such a facial expression of anger in the form of graphic art with technique Relief print.Methods in porses of making this work is done through perujutan ideas of art with several steps: Preparation (preparation), Elaboration, Synthesis, Reality Concept, Phase Completion (finishing)These works are created through various processes and experiences in the life of the author himself. As for the work that the author created was entitled: 1. Anger, 2. Ignorant, 3. Do not Want to Know, 4. Need 5. Who Cares, 6. Annoyed, 7. Wrath, 8. Upset, 9. Hurt , 10. Bored.Keywords: Expression of Emotions Anger, Graphic Arts, Print Relief.